5-2x=3+3x-4x

Simple and best practice solution for 5-2x=3+3x-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5-2x=3+3x-4x equation:


Simplifying
5 + -2x = 3 + 3x + -4x

Combine like terms: 3x + -4x = -1x
5 + -2x = 3 + -1x

Solving
5 + -2x = 3 + -1x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add 'x' to each side of the equation.
5 + -2x + x = 3 + -1x + x

Combine like terms: -2x + x = -1x
5 + -1x = 3 + -1x + x

Combine like terms: -1x + x = 0
5 + -1x = 3 + 0
5 + -1x = 3

Add '-5' to each side of the equation.
5 + -5 + -1x = 3 + -5

Combine like terms: 5 + -5 = 0
0 + -1x = 3 + -5
-1x = 3 + -5

Combine like terms: 3 + -5 = -2
-1x = -2

Divide each side by '-1'.
x = 2

Simplifying
x = 2

See similar equations:

| 8x+10-(2x+5)=-55 | | -2(m-60)=-m | | 5m=3m+6 | | 9x=2x^2-18 | | 8x-12=15x+10 | | 6x+12=-6 | | 4+p^2+12p=0 | | 2(x-3)=x+9 | | X^2+7x-38=0 | | x^2+50x+336=0 | | 4x+12=-2(x-3) | | -3(2x-1)=4-3x | | x^2-8x-1008=0 | | s-31=20.6 | | 6x+2=8x-2 | | x^2-4x-320=0 | | 7.2+c=19 | | 25(y+1)-x^2(y+1)= | | -2x-1=0 | | x^2+43x+432=0 | | x+0.08x=4.32 | | 6a+10=4a+16 | | r^2+5r+4= | | 2x+2=7x-2 | | (3x^2-7x-6)+(-3x+2)= | | 8x^2-14x+3= | | 4(2c+3)7=13 | | 456=-130r-60r | | 5x-3=3.5x | | 11m(21m+10)=0 | | 4x+2=14x-6 | | (9x-4)(x-1)= |

Equations solver categories